Розробка елементів онлайн системи формування та моніторингу замовлення у ресторані - Височин, А. О. (ХНУРЕ, 2024)
The work will look at how electronic order acceptance is easier than live in person-to-person interaction, how it simplifies the process and saves time. The application description describes the architecture and implementation of the software. The essence of the application will be to optimize the work of the restaurant with the ability to conveniently place an order, pay for your order online, track the time of its preparation, at what stage of cooking the dish is, and upon delivery, where is the courier with your order.
Keywords: замовлення у ресторані; ресторан